Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Suku Dinas Penanggulangan Kebakaran Dan Penyelamatan Kota Administrasi Jakarta Selatan - Muhamad Akbar Sobirin; Henni Marlinah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to determine the influence of work discipline and work environment on employee performance at the South Jakarta City Administration Fire and Rescue Sub-dept. both partially and simultaneously. The method used in this research is quantitative. This research took a sample and population of 233 respondents with a sample of 70 respondents using sample sampling. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Partially testing the hypothesis for the work discipline variable obtained tcount > ttable or (4.073 > 1.99601). This was also confirmed by the ρ value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant influence between work discipline and employee performance. Partially testing the hypothesis for work environment variables obtained tcount > ttable or (5.396 > 1.99601). This is also confirmed by the ρ value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant influence between the work environment on employee performance. Simultaneous hypothesis testing obtained Fcount > Ftable or (21.830 > 3.103). This was also confirmed by the ρ value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant simultaneous influence between work discipline and work environment on employee performance. The coefficient of determination obtained by the R-square value is 0.395, so it can be concluded that the work discipline and work environment variables influence employee performance variables by 39.5% while the remaining 60.5% is influenced by other factors not explained in this research such as leadership, compensation, work stress, etc